Music in twentieth-century Oxford : new directions - Darwall-Smith, Robin; Wollenberg, Susan (Boydell Press, 2023)
"The first book length study of musical education and culture in twentieth century Oxford. Music has always played a central role in the life of Oxford, in both the city and university, through the great collegiate choral foundations, the many amateur choirs and instrumentalists, and the professional musicians regularly drawn to perform there. Oxford, with its collegiate system and centuries-long tradition of musical activity, presents a distinctive and multi-layered picture of the role of music in urban culture and university life"--